Dampak Teknik Relaksasi Benson terhadap Kecemasan pada Pasien Pre Tindakan Multi-Slice Computed Tomography Cardiac (Journal of Telenursing (JOTING), 2025)
This study aims to measure the effect of Benson's relaxation technique on the anxiety level of pre-cardiac MSCT patients. This study used a quantitative method with a pre-experimental approach through a one-group pretest-posttest design. The results showed a significant decrease in anxiety scores after the intervention (average initial score of 22.43 to 15.27 after the intervention). Benson's relaxation technique has been proven effective in reducing anxiety, especially in the psychic and somatic dimensions. In conclusion, Benson's relaxation technique has been proven effective in reducing anxiety levels of pre-cardiac MSCT patients. This is indicated by a significant decrease in the average anxiety score of patients based on measurements using the Hamilton Anxiety Rating Scale (HARS).Keywords: HRS-A, Intervention, Anxiety, Cardiac MSCT, Benson's Relaxation